2019
DOI: 10.3389/fphar.2019.00762
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Indolizine Derivative Induces Apoptosis Through the Mitochondria p53 Pathway in HepG2 Cells

Abstract: Indolizine derivatives are a class of compounds with excellent biological activity. In this study, a series of indolizine derivatives, compound 1 (C1), compound 2 (C2), compound 3 (C3), and compound 4 (C4), were synthesized. 3-(4,5-dimethylthiazole)-2,5-diphenyltetraazolium bromide (MTT) assay was used to evaluate their cytotoxicity against HepG2 (p53-wild), A549, and HeLa cell lines. HepG2 cells apoptosis induced by C3 was determined using Hoechst staining and acridine orange/ethidium bromide staining. Cells’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Channels are open enough to release apoptotic factors such as cytochrome c from mitochondria into the cytoplasmic matrix, causing cell death . Mitochondrial apoptotic pathway is characterized as the increase of mitochondrial membrane potential and reactive oxygen . Here, it was found that ANRIL overexpression increased D‐loop expression, resulted in a higher ATP level, enhanced mitochondrial membrane potential, and increased mitochondrial marker expression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Channels are open enough to release apoptotic factors such as cytochrome c from mitochondria into the cytoplasmic matrix, causing cell death . Mitochondrial apoptotic pathway is characterized as the increase of mitochondrial membrane potential and reactive oxygen . Here, it was found that ANRIL overexpression increased D‐loop expression, resulted in a higher ATP level, enhanced mitochondrial membrane potential, and increased mitochondrial marker expression.…”
Section: Discussionmentioning
confidence: 98%
“…However, the roles of ANRIL in regulating mitochondrial function are never been revealed. The main pathways of apoptosis are as follows: the external pathway is called death receptor pathway and the internal mode is mainly mitochondrial endogenous apoptosis . The second main function of mitochondria is to participate in cell energy metabolism, which affects ATP production through respiratory chain.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, MCNs also demonstrated anti-apoptotic effects. To identify the protection mechanism, we assessed ROS production and mitochondrial membrane potential changes, which are closely related to apoptosis 50 . Increased ROS production inducing apoptosis was verified in Figure 5 E-F .…”
Section: Resultsmentioning
confidence: 99%
“…HIF-1 can induce apoptosis through stabilization of wild-type p53, whereas it prevents apoptosis in the mutant p53 gene. HepG2 is the only HCC cell that has wild type p53 [38]. Moreover, HIF-1A can induce apoptosis via an increase in the stability of the product of the tumor suppressor gene p53.…”
Section: Discussionmentioning
confidence: 99%